Role of UHRF1 in malignancy and its function as a therapeutic target for molecular docking towards the SRA domain. (September 2019) - Polepalli, Sravani; George, Sophia M; Valli Sri Vidya, R; Rodrigues, Gabriel Sunil; Ramachandra, L.; Chandrashekar, Raghu; M, Deepak Nayak; Rao, Praveen P.N.; Pestell, Richard G.; Rao, Mahadev
Graphical abstract: Highlights: UHRF1 is upregulated in several cancers. UHRF1 levels are associated with stage, size and grade of the tumor. UHRF1 can be used as a druggable target. Docking of Propranolol, Nocodazole, Thymoquinone, Emodin, Napthazarin to SRA domain. Abstract: The figure describes the location of UHRF1 (Ubiquitin-like with containing PHD and RING Finger domains 1) gene, mRNA and protein synthesis in the tumor cell and its structural domains with a focus on the docking of Naphthazarin on the SRA domain of UHRF1, resulting in reduction of tumor size.